The Investigation of Geography Teacher Candidates Opinions' Towards Values Education - (:unkn) unknown (MARMARA UNIV, 2017)
This study was conducted in order to determine opinions of the geography teachers towards values education. Qualitative phenomenological research design was used in this study. Participants were chosen using purposive sampling technique. In this context, 8 fifth grade candidates of geography teachers participated and 4 of the candidates of teachers are female and 4 of them are male. The data of the semi-structured interview form were selected with the help of expert opinion. The data that were processed using descriptive method. As a general result of the research, it has been determined that the undergraduate program applied to train geography teachers does not have the desired quality towards values education to candidates. The sub-outcomes that led to this conclusion of general outcome were presented in findings and discussions sections in the context of research aims.
Keywords: Geography teaching; value; values education; teacher candidate; CHARACTER EDUCATION